Legal Politics Deconcentration Study on Post-Reform Regional Development Planning - Habib Muhsin Syafingi (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The principle of deconcentration is a necessity in the era of decentralization to ensure the establishment of Indonesian unitary state. The dynamics of drafting laws and regulations are actually an effort to find the most appropriate format in managing the relationship between the centre and the regions, in the sense of how to accommodate the centre's interests without stifling creativity and regional initiatives in planning development. This article tries to examine the dynamics of deconcentration in post-reform regional development planning. The period is divided into the 2004-2014 and 2014-2019 periods, each period marked by the issuance of a series of laws and regulations, each period reflecting a certain policy direction (legal politics) of deconcentration. This research is normative juridical research with a statutory approach in which the data obtained will be analyzed qualitatively and presented descriptively. The research results show that in the 2004-2014 period, deconcentration tends to be a complement and a formality to maintain a unitary state, while in the 2014-2019 period, deconcentration appears to be stronger in line with the authority of decentralization. The similarity in these two eras is that the implementation structure of deconcentration still overlaps with the structure of decentralization, thus allowing confusion and overlapping. The research results show that in the 2004-2014 period, deconcentration tends to be a complement and a formality to maintain a unitary state, while in the 2014-2019 period, deconcentration appears to be stronger in line with the authority of decentralization.